2022
DOI: 10.3390/nu14132642
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements in People with Metastatic Cancer Who Are Experiencing Malnutrition, Cachexia, Sarcopenia, and Frailty: A Scoping Review

Abstract: Cancer-associated malnutrition, or cachexia, stemming from cancer or its treatments, is particularly prevalent in metastatic cancers, and is often interrelated with sarcopenia and frailty. Evidence suggests that dietary supplements play a role in managing these conditions. As metastatic cancer cells are associated with notable genomic and phenotypic alterations, response to dietary supplements may differ between metastatic and non-metastatic cancers. However, research in this area is lacking. This scoping revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The nutraceuticals covered were broad; vitamins, minerals, antioxidants, proteins, amino acids, and fatty acids among them. The authors concluded that overall a consistent positive impact for multimodal treatments, and for omega-3-fatty acid supplementation was observed, but it was difficult to obtain as clear a picture for the other nutraceuticals primarily due to insufficient data [17]. The fourth paper in this series was published much earlier -in 2013 -and is an SR of reports on nutritional intervention roles for head and neck squamous cell cancer patients' who are undergoing radiotherapy or chemotherapy [18].…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The nutraceuticals covered were broad; vitamins, minerals, antioxidants, proteins, amino acids, and fatty acids among them. The authors concluded that overall a consistent positive impact for multimodal treatments, and for omega-3-fatty acid supplementation was observed, but it was difficult to obtain as clear a picture for the other nutraceuticals primarily due to insufficient data [17]. The fourth paper in this series was published much earlier -in 2013 -and is an SR of reports on nutritional intervention roles for head and neck squamous cell cancer patients' who are undergoing radiotherapy or chemotherapy [18].…”
Section: Cancermentioning
confidence: 99%
“…A paper published this year (2022) attempted a more ambitious screen. Johal et al, reviewed reports on the impact of nutritional interventions for patients with metastatic cancer experiencing cancer-associated malnutrition, sarcopenia and frailty [17]. Of over 8000 initial records they selected, 48 papers (18 RCTs among them) met their inclusion criteria for this scoping review.…”
Section: Cancermentioning
confidence: 99%
“…It was also noted that cancer patients had markedly altered circulating amino acids, especially EAAs, and this varied depending on patients’ weight loss, nutrition and metastasis, which is why plasma amino acids could play a potential role as biomarkers for diagnosis and screening cancer patients [ 46 ]. Miyagi et al demonstrated that gastric cancer had reduced plasma amino acids [ 34 , 47 ]. Over time, however, anabolic resistance is seen in cancer cachexia in advanced disease—this is where the body’s tissues become less responsive to anabolic stimuli such as external amino acids.…”
Section: Natural Anti-inflammatories and Their Derivativesmentioning
confidence: 99%
“…Over time, however, anabolic resistance is seen in cancer cachexia in advanced disease—this is where the body’s tissues become less responsive to anabolic stimuli such as external amino acids. This process contributes to muscle wasting and is one of the reasons that nutritional support alone cannot reverse cancer cachexia [ 33 , 47 ].…”
Section: Natural Anti-inflammatories and Their Derivativesmentioning
confidence: 99%
“…Diet-related unmet care needs, including poor appetite and gas­trointestinal symptoms, are common among those with cancer [6]. Malnutrition is common in cancer patients and is caused by an impaired ingestion or assimilation of nutrients, which is connected either to the cancer itself or its specific treatments [4].…”
Section: Knowledge Transfer Of Laura Keaver (Sligo) and Bruno Abreu (...mentioning
confidence: 99%